1999
DOI: 10.1210/en.140.9.4089
|View full text |Cite
|
Sign up to set email alerts
|

Growth Hormone and Insulin-Like Growth Factors Have Different Effects on Sebaceous Cell Growth and Differentiation

Abstract: Several observations suggest that GH stimulates sebaceous gland growth and development. Therefore, we studied the effects of GH and insulin-like growth factors (IGFs), alone and with androgen, on sebaceous epithelial cell (sebocyte) growth and differentiation in vitro. The rat preputial cell culture model system was used to judge differentiation (induction of lipid-forming colonies, LFCs) and DNA synthesis. GH increased sebocyte differentiation. At a dose of 10(-8) M in the presence of micromolar insulin, GH w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
100
0
2

Year Published

2002
2002
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(108 citation statements)
references
References 0 publications
6
100
0
2
Order By: Relevance
“…Increased serum levels of IGF-I have been observed in adult women and men with acne and the number of total acne lesions, inflammatory lesions, serum levels of 5α-DHT and dehydroepiandrosterone sulphate (DHEAS), each correlated with serum IGF-I levels in women with acne [90]. IGF-I plays a key role in the induction of lipid synthesis in human sebocytes [91,92]. IGF-I increases lipogenesis by inducing SREBP-1 [50] through activation of PI3K/Akt and MAPK/ERK-signal transduction pathway [93].…”
Section: Sex Steroidsmentioning
confidence: 99%
“…Increased serum levels of IGF-I have been observed in adult women and men with acne and the number of total acne lesions, inflammatory lesions, serum levels of 5α-DHT and dehydroepiandrosterone sulphate (DHEAS), each correlated with serum IGF-I levels in women with acne [90]. IGF-I plays a key role in the induction of lipid synthesis in human sebocytes [91,92]. IGF-I increases lipogenesis by inducing SREBP-1 [50] through activation of PI3K/Akt and MAPK/ERK-signal transduction pathway [93].…”
Section: Sex Steroidsmentioning
confidence: 99%
“…53 The expression of IGF-I receptor mRNA is the strongest in basal cells of sebaceous glands and immature sebocytes, whereas IGF-I receptor protein expression was uniform and intense in all regions of the gland. 53 In animal studies, IGF-I has been shown to stimulate sebocyte differentiation in vitro especially in combination with GH, 47 while in human keratinocytes it acts as a mitogen. 54 On the other hand, in humans, IGF-I plays a key role in the induction of lipid synthesis in human sebocytes.…”
Section: Effects Of Hormones On Sebaceous Gland Cellsmentioning
confidence: 99%
“…46 In acne vulgaris, increased sebum production peaks in mid-adolescence at a time that GH and IGF-I reach their highest serum levels. 47 In mini rats, suppression of GH gene expression by an antisense transgene, leads among to thinner skin with less collagen and increase of subcutaneous adipose tissue also to small-sized sebaceous glands. 48 Increased serum levels of IGF-I have been observed in adult women and men with acne and the number of total acne lesions, inflammatory lesions, serum levels of 5α-DHT and DHEA sulphate, each correlated with serum IGF-I levels in women with acne.…”
mentioning
confidence: 99%
“…Moreover, IGF-I has been shown to stimulate sebocyte differentiation in vitro especially in combination with GH (Deplewski and Rosenfield, 1999), while in human keratinocytes it acts as a mitogen (Tavakkol et al, 1999). In acne vulgaris, increased sebum production peaks in mid-adolescence at a time that GH and IGF-I reach their highest serum levels (Deplewski and Rosenfield, 1999).…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…In acne vulgaris, increased sebum production peaks in mid-adolescence at a time that GH and IGF-I reach their highest serum levels (Deplewski and Rosenfield, 1999). IGF-I amplified lipid synthesis in SZ95 sebocytes and fibroblasts as well as fibroblast proliferation, all in a dose-dependent manner underlining the fact that the declining IGF-I levels with increasing age may play a significant role in the reduction of skin surface lipids and thickness (Makrantonaki et al, 2008).…”
Section: Accepted M Manuscriptmentioning
confidence: 99%